Case Report: Be Aware of “New” Features of Niemann–Pick Disease: Insights From Two Pediatric Cases - Chen, Fan; Guo, Shan; Li, Xuesong; Liu, Shengxuan; Wang, Li; Zhang, Victor Wei; Xu, Hui; Huang, Zhihua; Ying, Yanqin; Shu, Sainan (Frontiers in Genetics, 2022)
Niemann–Pick disease is a relatively common lysosomal storage disease. Cholestatic liver disease is a typical clinical phenotype of Niemann–Pick disease in infancy. The diagnosis is traditionally based on Niemann–Pick cells in bone marrow smears or liver biopsies. Treatment for cholestatic liver disease mainly includes ursodeoxycholic acid and liver protection drugs. Here, we reported two cases of Niemann–Pick disease type C, diagnosed by genetic analysis during early infancy. Besides cholestatic jaundice, the two patients also exhibited signs of immune system hyperactivity, such as elevated immunoglobulins or multiple autoantibodies, which might require the application of glucocorticoids. In addition, three novel missense variants of the NPC1 gene were identified. The findings suggest that immune activation should be considered as a “new” clinical phenotype of lysosomal storage diseases.